Breating 100% O2 has no effect on blood lactate concentration during a short passive recovery from exhaustive exercise - Kay, B.; Walker, H.; Barnao, D.; Graham, I.; Stannard, S.; Morton, H. (Journal of Sports Science & Medicine, 2005)
The practical utility of breathing 100% O2 for up to 5-minutes immediately following incrementally elicited acute muscular exhaustion is yet to be determined with respect to repeat exercise performance. If a performance increment is apparent from future investigation, it appears unlikely to be attributable to improved rates of blood LAclearance. Longer exposures to 100% O2 and/or different exercise modalities could be investigated in future if sport specificity justifies it; however the safety of this should be determined first.